Reconsidering the family unit, augmenting the child through architecture. - Tarry, Mary-Lee (My University, 2014)
Focussing specifi cally on orphaned and abandoned children, this thesis aims to merge theories of psychology and phenomenology within the scope of empathic architecture. Psychology has become a common consideration in architecture, as it addresses the psychological impact of building forms. Phenomenology examines the way a person experiences space and environment. Architectural theorists have discussed how phenomenology is the process of orientating oneself within the environment, whilst psychologically the orientation process is cognitive and it is the brain that generates a perception of space, thus providing a balance between a person and her environment. Empathic architecture is the physical representation of this balance, as it is able to evoke an emotional dialogue with the user, who in turn identifies a connection between both building and environment. Through inter-subjective processes, this thesis explores the orphaned or abandoned child’s place within contemporary society. It observes how the built forms, programs and external environments (which provide methods of orphan- care) are either a pro-active or reactive portrayal of how these children are being provided for. A further examination is made on how society is accommodated within the city and the possible improvements are proposed, with respect to caring for the orphan child, through the reintegration of the community. The main conclusion that can be drawn from the thesis is that, through the combined application of psychological and phenomenological principles, it is possible to create empathic architecture which meets the needs of the user. This user is then able to connect with the building and environment and thus create the basis for communal reintegration. This thesis concludes with the Developmental Orphanage for Children; a building which provides innovative methods of community integration, centred on the child user, that aims at facilitating new approaches to the conventional prototypes of institutional and residential suburban building models.